2006
DOI: 10.1039/b602906j
|View full text |Cite
|
Sign up to set email alerts
|

Selective coulometric release of ions from ion selective polymeric membranes for calibration-free titrations

Abstract: Coulometry belongs to one of the few known calibration-free techniques and is therefore highly attractive for chemical analysis. Titrations performed by the coulometric generation of reactants is a well-known approach in electrochemistry, but suffers from limited selectivity and is therefore not generally suited for samples of varying or unknown composition. Here, the selective coulometric release of ionic reagents from ion-selective polymeric membrane materials ordinarily used for the fabrication of ion-selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…Recently, it has been found that the ion fluxes across the membrane can be modulated and controlled precisely by applying an external current [23,[30][31][32]. Previous reports have shown that ions across the polymeric membrane ion-selective electrode can be selectively and precisely delivered to the sample solution for calibration-free titrations [33]. Recently, Crespo et al developed a technique based on a thin layer Coulometry and revealed that protamine can be selectively transferred from a thin layer to the outer solution at a fixed applied potential [34].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been found that the ion fluxes across the membrane can be modulated and controlled precisely by applying an external current [23,[30][31][32]. Previous reports have shown that ions across the polymeric membrane ion-selective electrode can be selectively and precisely delivered to the sample solution for calibration-free titrations [33]. Recently, Crespo et al developed a technique based on a thin layer Coulometry and revealed that protamine can be selectively transferred from a thin layer to the outer solution at a fixed applied potential [34].…”
Section: Resultsmentioning
confidence: 99%
“…If spontaneous zero current ion fluxes are negligibly small, an imposed current pulse will deliver an defined quantity of material into the sample without any need for titrimetric standards or calibration procedures, with a very high degree of selectivity. This concept has just recently been demonstrated with a polymeric ion-selective membranes for the purpose of accurately delivering reagents [22]. Figure 4 demonstrates the coulometric delivery of calcium for the titration of EDTA.…”
Section: Constant Current Coulometry: Calibration Free Reagent Deliverymentioning
confidence: 99%
“…Figure 4 demonstrates the coulometric delivery of calcium for the titration of EDTA. Here, one ion-selective membrane was electrochemically controlled to deliver calcium ions, and a second ion-selective membrane of similar composition was used as the detector electrode [22]. The simple relationship between applied number of coulombs and expelled amount of ions (Faraday's law) coupled with the high ion selectivity of such membranes makes this a very promising technique to deliver reagents without the need for maintaining accurate standard solutions.…”
Section: Constant Current Coulometry: Calibration Free Reagent Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the ion flux of primary ions in the direction of the outer solution could be modulated by an external voltage or a current. 19 BuchE, as a target enzyme for pesticide determination and drug screening, can catalyze the hydrolysis of Buch. The ISE membrane potential generated by the surface Buch may therefore be sensitive to BuchE.…”
mentioning
confidence: 99%